JOLANTA BROŻEK (2013) A comparison of external and internal maxilla and mandible morphology of water bugs (Hemiptera: Heteroptera: Nepomorpha). Zootaxa, 3635(4), 340–378. - Brożek, Jolanta (Zootaxa, 2013)
Page 375 line 30 to read as: -Insufficient data were obtained on the monophyly of the Naucoridae, due to the output of the Cheirochelinae (one autapomorphy was indicated), and lack of synapomorphy in all subfamilies of the Naucoridae. The monophyly of Naucoridae had been indicated in a previous study by Hebsgaard et al., (2004).